Watts of Trust: Linking Union Roles and Leadership to Workforce Performance - Awang Asmoro; Riani Rachmawati (Eduvest - Journal of Universal Studies, 2025)
Purpose. This research examines the influence of union instrumentalism and transformational leadership on job performance, mediated by job security and job satisfaction. In promoting the effectiveness of organizational transformation, trade unions and transformational leadership play a crucial role in the sustainable management of human resources. Methods. Quantitative approach with Covariance Based SEM with a total of 370 respondents used for data analysis, using Lisrel. Findings (plan). The research findings reveal that the instrumentalism of labor unions is positively related to job security, job security mediates the relationship between the instrumentalism of labor unions and job performance, the instrumentalism of labor unions positively affects job satisfaction, transformational leadership has a positive relationship with job security, and job satisfaction mediates the relationship between transformational leadership and job performance. Originality/novelty. There are not many studies that integrate trade unions and transformational leadership to evaluate job performance in the context of organizational transformation, particularly in Indonesia. The contribution of this research to the literature is to provide empirical evidence regarding the impact of union instrumentalism and transformational leadership on job performance. Similar studies are still rare in Indonesia, thus enriching the research on the topic..